AN EMPIRICAL STUDY ON LENDING PATTERN AND PERCEPTION OF COMMERCIAL BANKS TOWARDS SMALL AND MEDIUM ENTERPRISES LENDING - M, Nandini; B N, Shubha (International Journal of Accounting & Finance Review, 2021)
Micro, Small and Medium sector (MSME) is the most dynamic sector due to its capacity for innovation, competence for advancements and perseverance to face multiple challenges. Though this sector contributes 8 per cent to GDP, 45 per cent towards manufacturing output and 40 per cent of exports. Still, they lack support to grow exponentially. Understanding the lending pattern of the banks and the perception of commercial banks towards MSME lending is essential not only for academic knowledge but also could necessitate policy changes. The objective of the research is to understand the lending pattern of banks to SMEs and the perception of commercial banks towards SME lending. The researcher used both primary and secondary data. Statistical tools ANOVA and Kruskal Wallis tests are used to analyze the collected data. The results indicate that there is no significant difference in the lending pattern of public sector banks, Private sector banks and foreign banks and the bank staff have a similar level of perception on difficulties in lending to SMEs, perception on the rejection of loan, perception on reluctance to serve SME sector, perception on loan default and factors affecting credit decisions irrespective of the type of the bank and experience in SME lending. JEL Classification Codes: G21, G23, G28.